Peningkatan Keterampilan Berbicara Menggunakan Model Cooperative Learning Tipe Example Non Example pada Peserta Didik di Kelas II SDN 18 Air Tawar Selatan Kota Padang - Zaki, Ahmad; Suriani, Ari (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the application of the Example Non Example Type Cooperative Learning model to improve the speaking skills of class II students of SDN 18 Air Tawar Selatan.This type of research is classroom action research using qualitative and quantitative approaches. This research was conducted in two cycles, cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle has four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and class II students totaling 23 people.The results of the cycle I teaching module research, meetings 1 and 2 obtained a percentage of 83.3% 87.5%, increasing in cycle II to 95.83%. Teacher activity in cycle I, meetings 1 and 2 obtained a percentage of 77.5% and 87.5%, increasing in cycle II to 97.5%. Student activity in cycle I, meetings 1 and 2 obtained a percentage of 77.5% and 90%, increasing in cycle II to 97.5%. The learning outcomes of student knowledge in cycle I, meetings 1 and 2 obtained an average of 75.65 and 79.56, increasing in cycle II to 88.26. The results of the skills assessment in cycle I, meetings 1 and 2 obtained an average of 78.07 and 81.62, increasing in cycle II to 87.85. Based on these results, it can be concluded that the Example Non Example Cooperative Learning model can improve the speaking skills of grade II elementary school students